The German Enforceable Notarial Act in Cross-Border Cases - Bormann, Jens (LeXonomica, 2022)
The subject of this article is to explain and discuss the legal framework for German enforceable notarial acts in cross-border traffic. The first part will illustrate the prerequisites for the enforcement of a notarial act in Germany, especially in circumstances when the creditor or debtor lives abroad. The second section is dedicated to the enforcement of German enforceable notarial acts abroad. After presenting the principles of international law, the main legislative acts regarding enforcement in the European and international framework will be analysed in detail. Povzetek. Predmet tega članka je razlaga in obravnava pravnega okvira za nemške izvršljive notarske listine v čezmejnem prometu. V prvem delu bodo prikazane predpostavke za izvršitev notarske listine v Nemčiji, zlasti v okoliščinah, ko upnik ali dolžnik živi v tujini. Drugi del je namenjen izvrševanju nemških izvršljivih notarskih listin v tujini. Po predstavitvi načel mednarodnega prava bodo podrobno analizirani glavni zakonodajni akti v zvezi z izvrševanjem v evropskem in mednarodnem okviru.